Characteristics of Water Pollution and Evaluation of Water Quality in Subsidence Water Bodies in Huainan Coal Mining Areas, China - Xinyue Deng; Guangzhou Chen (Journal of Chemistry)
The subsidence water bodies in coal mining areas are vulnerable to being polluted by the surrounding mining production wastewater, domestic sewage, and agricultural return flow. Therefore, it is important to grasp the water quality condition of the above water bodies. A total of 16 surface water samples from 7 different subsidence water bodies in the Huainan mining area were collected and focused on the selection of 22 water quality indicators for water pollution characteristics analysis. The result of correlation analysis showed that Cr and Zn came from the same source of pollution. Three principal factors were selected by factor analysis, which could explain 82.294% of the total variance. Principal factor 1 indicated a mixture of pollution related to nitrogen and phosphorus nutrients, organic pollutants, and heavy metals; principal factor 2 showed heavy metal pollution; and principal factor 3 presented the pollution from heavy metals and cations. Results of cluster analysis showed that the water quality status of 16 sampling points could be divided into 4 clusters. The results of the heavy metal pollution index method showed that the heavy metal pollution was most serious in sample 9 (S9), S15, and S16, and the main elements of pollution were Ni, Fe, and Mn. Single-factor evaluation, comprehensive pollution index, the universal exponential formula of logarithmic power function, and membership degree method were used to evaluate the five important water quality indicators, namely total nitrogen, ammonia nitrogen, total phosphorus, dissolved oxygen, and chemical oxygen demand. The results showed that the total nitrogen pollution in the study area was more serious, most of the sites exceed class V standards of the surface water, S14 and S16 were heavily polluted. Based on the comparison of the different methods, the surface water quality in the study area can be reflected more comprehensively.